Exploring the Situational Factor at Work: On Time Banditry - Yulianti, Praptini; Khaira, Nurul; Yuningsih, Yuyun (Universitas Airlangga, 2024)
Objective: Time banditry behavior is often overlooked as counterproductive work behavior (CWB) even though it has a hidden negative impact and can disrupt organizational performance. This study will explore situational factors sourced from the organization, namely narcissistic leadership, workload, and boredom, that trigger stress at work, namely emotional exhaustion. Emotion exhaustion will impact time banditry behavior. Design/Methods/Approach: This study involved 181 civil servants in western Indonesia. Data were collected through a survey and analyzed using partial least squares-structural equation modelling (PLS-SEM). Findings: The findings revealed that narcissistic leadership and boredom have a significant and positive influence on time banditry behavior; boredom at work also has a significant and positive effect on time banditry. Meanwhile, boredom at work has the greatest influence on time banditry. Workload has a significant and negative influence on time banditry behavior. There are two insignificant influences, namely emotional exhaustion to time banditry behavior and narcissistic leadership to emotion exhaustion. Furthermore, both workload and boredom have a significant and positive influence on emotional exhaustion. Originality/Value: This study provides theoretical and practical contributions to the workplace that can trigger time banditry. Situational factors, including narcissistic leadership, workload load, and boredom, can cause emotional exhaustion. They will do time banditry. Practical/Policy Implications: The results of this study have practical implications, such as boredom at work being prone to trigger the emergence of time banditry behavior. Organizations need to redesign work so that work is more varied and less boring through rotation, transfer, or job enrichment arrangements and job functions.